An Analysis on the Students’ Errors in Pronouncing English Vowel - Adawiyah, Robiatul; Retnowati, Nanik (ENGLISH JOURNAL, 2016)
This present research is aimed at finding out the kinds of errors made by students in pronouncing English vowels and identifying the ones which often appear. The writers used test that implemented in reading text. Then, they analyzed the errors that the students made in their reading and calculated them using simple statistic formula. There were 20 students in this study. Those who became the sample were the students who have attended the subject of Pronunciation Practice in the previous year. The result shows that the students’ pronunciations of English vowels were “good”, according to criterion but they still made errors; some errors were finally revealed.